YUZA VA HAJMNI HISOBLASh USULLARI HAQIDA - Abjalilov, S.X.; Arzikulova, M.H.; Abdisalomova, H.Y. (SCIENCE and SOCIETY, 2025)
The article discusses the axiomatic introduction of the concepts of area and volume, the possibility of measurement as a numerical value, as well as several methods of calculation.
Keywords: square and cubic unit; invariance and additivity; quadrature figures; triangle; polygon